1992
DOI: 10.2307/1591507
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Salmonella enteritidis Isolates from Maine Poultry and Poultry Farm Environments

Abstract: Eighty-six Salmonella enteritidis isolates obtained during a surveillance program of poultry farms in Maine were subjected to phage-typing, plasmid profiling and fingerprinting, outer-membrane polypeptide analysis, and antimicrobial sensitivity testing. Isolates were obtained from a variety of sources, including poultry-farm environmental samples, chicken organ samples, human stool samples, cat feces, and live-trapped rats and mice. These isolates were compared with 21 S. enteritidis isolates originating outsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In our study we found a similarity of plasmid sizes on specific farms and this could be due to preferential carrying of plasmids by specific PTs (predominant on those farms) or to transmission of these elements within bacteria on the farms. Several other studies have shown that multiple plasmid profiles can be seen among isolates of the same phage type and conversely that isolates assigned to different phage types can exhibit the same plasmid profile (30,40). This observations would suggest the possibility of plasmid transmission within isolates of different phage types.…”
Section: Figmentioning
confidence: 79%
“…In our study we found a similarity of plasmid sizes on specific farms and this could be due to preferential carrying of plasmids by specific PTs (predominant on those farms) or to transmission of these elements within bacteria on the farms. Several other studies have shown that multiple plasmid profiles can be seen among isolates of the same phage type and conversely that isolates assigned to different phage types can exhibit the same plasmid profile (30,40). This observations would suggest the possibility of plasmid transmission within isolates of different phage types.…”
Section: Figmentioning
confidence: 79%
“…A latex particle agglutiThorns and colleagues [26] did not react with all other serotypes; however, it agglutinated Dublin. Other methods based on gene restriction fragment patterns [27,28] and plasmid profile analyses [29] rely on DNA isolation and restriction digestion, which require several days to complete.…”
Section: Discussionmentioning
confidence: 99%
“…A partial list of non-mammalian wildlife that have been demonstrated to carry Salmonella and could potentially come in contact with feed sources and food production animals include toads, vultures, lizards, tree frogs, and wild passerine birds (Everard et al, 1979;Kapperud et al, 1998). A partial list of documented infected and / or carrier mammalian species include rats, mice, Sika deer, mongooses, bats, monkeys, and opossums (Thigpen et al, 1975;Everard et al, 1979;Henzler and Opitz, 1992;Singer et al, 1992;Sato et al, 2000). Domestic cats and companion animal facilities have also been shown to be problematic for Salmonella (Singer et al, 1992;van Immerseel et al, 2004a;Wright et al, 2005).…”
Section: Potential Risk Factors For Salmonella Feed Contaminationmentioning
confidence: 99%
“…A partial list of documented infected and / or carrier mammalian species include rats, mice, Sika deer, mongooses, bats, monkeys, and opossums (Thigpen et al, 1975;Everard et al, 1979;Henzler and Opitz, 1992;Singer et al, 1992;Sato et al, 2000). Domestic cats and companion animal facilities have also been shown to be problematic for Salmonella (Singer et al, 1992;van Immerseel et al, 2004a;Wright et al, 2005). Insects represent an additional potential carrier of Salmonella spp.…”
Section: Potential Risk Factors For Salmonella Feed Contaminationmentioning
confidence: 99%